PREDICTORS OF THE FORMATION AND FEATURES OF THE CLINICAL PICTURE OF ADJUSTMENT DISORDERS - Isakov, R.I.; Herasymenko, L.O.; Kydon, P.V.; Fysun, Yu.O.; Belov, O.O.; Pshuk, N.G.; Skrypnikov, A.M. (World of Medicine and Biology, 2023)
The war in Ukraine influenced the the emergence of a significant number of people who have suffered severe psychological trauma and need forehanded, modern and effective medical care. The purpose of the study was to investigate the predictors of the formation of adjustment disorders and the features of the course and differences in the clinical picture of adjustment disorders during the war in Ukraine. The following methods were used to achieve the purpose and implementation of the tasks of this study: information-analytical, clinical-anamnestic, clinical-psychopathological, psychodiagnostic, psychometric and statistical methods of mathematical processing of the obtained results. According to the results of the conducted research, it was found that the main predictors of the formation of adaptation disorders are forced relocation, both within the country and abroad, and especially during which a person feels the influence of a stress factor, in particular, and experiencing negative emotions for a long time.
Keywords: adjustment disorders; internally displaced persons; stress; depression; anxiety